Body mass index, weight, and height percentiles in school-aged children from Mendoza. A comparison with the WHO reference - Garraza, Mariela (2023)
Introduction. The World Health Organization (WHO) recommends the use of reference tables to monitor the growth pattern and nutritional status of children and adolescents. Body mass index (BMI), weight, and height are the most commonly used variables. The objective of this study was to estimate the BMI, weight, and height percentiles for school-aged children (2009-2011) living in the department of San Rafael (Mendoza) and compare them to the international World Health Organization reference to establish their relevance for the evaluation of the growth pattern and nutritional status of this population. Population and methods. A cross-sectional anthropometric study was conducted in 3448 school-aged children aged 4.00 to 13.49 years. The LMS ChartMarker Pro software was used to estimate the BMIfor- age, weight-for-age, and height-for-age percentiles, by sex and age, and they were compared with the WHO curves. Besides, percentage differences (%D) were calculated to estimate the differences and their statistical significance using the Wilcoxon test. Results. The population of boys and girls in San Rafael showed higher weight and BMI (%D ≈ 7% and 9%, respectively) percentiles, and lower height (%D ≈ 0.8%) values than WHO reference (p < 0.05). Conclusion. The differences found warn about the use of the WHO reference in the school-aged population of San Rafael since it would overestimate the prevalence of overweight, obesity, and chronic malnutrition and underestimate the prevalence of acute and global malnutrition. This situation highlights the importance of having a local reference resource.